The many faces of pulmonary metastases of osteosarcoma: Retrospective study on 283 lesions submitted to surgery. Issue 12 (December 2015) - Ciccarese, Federica; Bazzocchi, Alberto; Ciminari, Rosanna; Righi, Alberto; Rocca, Michele; Rimondi, Eugenio; Picci, Piero; Bacchi Reggiani, Maria L.; Albisinni, Ugo; Zompatori, Maurizio; Vanel, Daniel
Highlights: Atypical metastases of osteosarcoma were never described in big series. Previous large studies concluded that CT missed nearly the 25% of nodules. We found that up to 14% of metastases are not nodular (wide variability in shape). One third of metastases with atypical shape were represented by striae. The identification of atypical metastases could improve CT accuracy. Abstract: Objective: CT is the recommended technique for the detection of pulmonary metastases in patients affected by osteosarcoma, though claimed to show several limits compared to manual palpation. We retrospectively analyzed CT features of suspected lesions submitted to surgery to address its current accuracy and to investigate criteria for predicting histology. Materials and methods: CT scans of 70 patients submitted to thoracotomy between 2007–2013 were reviewed. Overall, 123 thoracotomies were performed and 283 lesions seen on CT were resected. Shape, size, presence and type of calcification, evolution of each lesion were analyzed. Number and histology of nodules detected at thoracotomy were recorded and compared to CT data. Results: 234/283—82.7% Lesions were metastases; 143—61.1% were calcified; most metastases were nodular (201/234—85.9%), but in 33/234—14.1% other findings were detected (striae, consolidations, pleural plaques/masses, cavitations, ground glass opacities, irregular shapes, halo sign). Malignant lesions were more frequently calcified, larger, with progression over time —p < 0.0001. Manual palpation identified 314 lesions, 248 metastatic—79.0%: CT missed 31/314—9.9% lesions, whereof 14/31—45.2% were metastases. Conclusions: Though most lesions are nodular and calcified, up to 40% are not calcified and atypical findings are not uncommon (14.1%). The identification of the atypical radiological presentation of metastases could be the key for improving CT accuracy.